“Our Legislative Bodies, Ourselves”: A Case Example of Integrating Experiential Civic Education and Public Health Advocacy Into Graduate Curricula - Nora Kenworthy; Jody Early (Pedagogy in Health Promotion, 2026)
At a time of heightened political polarization and public health politicization, educating students about advocacy and civic engagement is essential. While public health accrediting bodies and professional organizations recognize the importance of advocacy as a key competency, a limited number of training programs scaffold integrated training in advocacy, communication, and civic engagement as a core part of curriculum. In this paper, we describe how the Master’s program in Community Health and Social Justice at the University of Washington Bothell has incorporated advocacy, communication, and civic engagement into its core curriculum through two interlinked courses using experiential civic health education. These courses train and empower students as civic health leaders by working in partnership with community partners, stakeholder coalitions, public health advocates, and the state legislature in a praxis-oriented pedagogy. In this article, we describe the justifications for, and pedagogical groundings of, our approach before describing how the course leverages real world practice and community-based learning activities as the foundation of civic health education. Finally, we discuss challenges, opportunities, and lessons learned for incorporating these approaches in other settings.